Pelayanan prima resepsionis dalam menerima tamu pada marketing office Paradise Resort Ciputat Tangerang Selatan - Oktarini , Riri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study aims to determine the excellent service provided by the receptionist to guests or customers of Marketing Office Paradise Resort Ciputat, South Tangerang. In this research, observation and decision research methods are used. The results of this study are receptionist handling in improving excellent service at the Marketing Office Paradise Resort Ciputat South Tangerang, namely, the receptionist must always stand by at the reception desk, or when the receptionist has a need that requires leaving the place, there should be a temporary replacement so that consumers or guests visiting are not confused about asking for help, and when there is an incoming call, it is not ignored, because often the reception desk is empty during lunch hours or when the receptionist is on holiday and there is a need that requires leaving the reception desk. Constraints experienced by the receptionist at the Marketing Office Paradise Resort Ciputat, South Tangerang, namely the lack of experience or flying hours gained by the receptionist because the receptionist is still a fresh graduate, he still cannot handle the work that must be done if there are more than two jobs at the same time.